Analysis of the quality life the patients with vitiligo in the city São Luís - Maranhão (Research, Society and Development, 2020)
Vitiligo is considered a disease characterized by acquired depigmentation, caused by the decrease or absence of melanocytes, causing the appearance of white patches on the skin. This study purposed to evaluate the quality of life of a group of patients with vitiligo in a reference unit in the treatment of the disease. This is an observational and descriptive study of data collection, with a quantitative approach, developed at the Pam-Diamante Medical Specialties and Diagnosis Center located in the city of São Luís / Maranhão. Twenty-seven patients were enrolled, by convenience sample, diagnosed with vitiligo. The data were collected through a questionnaire prepared by the researcher, consisting of 12 questions regarding age, sex, clinical and psychological data. The mean age of the participants was 50.3 ± 17.1 years. The sample consisted mostly of women (74.1%). Most participants reported having problems in accepting the disease (51.9%). All interviewees had their quality of life affected in some way by the disease, were restricted in leisure and social practices among individuals, presenting a variety of negative feelings in relation to vitiligo. Thus, we concluded that the disease has a great impact on the quality of life of patients, affecting the acceptance of the disease, the relationship with people and causing feelings of sadness.